2016
DOI: 10.5588/ijtld.14.0848
|View full text |Cite
|
Sign up to set email alerts
|

Understanding NIH clinical case definitions for pediatric intrathoracic TB by applying them to a clinical trial

Abstract: Setting and Objective Currently, standardized clinical case definitions represent the best option for pediatric tuberculosis (TB) disease diagnosis and classification. We applied clinical case definitions for intrathoracic TB classification, developed by an expert panel for use in reporting diagnostic studies with passive case finding, to TB suspects from IMPAACT P1041, a trial of INH prophylaxis in healthy HIV-exposed, BCG vaccinated infants which employed active surveillance, to assess novel application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Definitions will need to be developed for different scenarios such as involving active case finding, for example, during household contact studies, but this is outside the present scope of work. Evaluation of data from active case-finding studies, one as a cohort study with active follow-up [23] and the other as a community-based tuberculosis contact investigation study [24], have reported that 12% and 65%, respectively, of children with confirmed tuberculosis did not have clinical features consistent with the standardized "clinical signs/symptoms suggestive of tuberculosis" used to categorize clinical, unconfirmed cases. Active case finding is likely to identify cases at an earlier stage of disease and a much shorter duration of symptoms compared with children investigated for tuberculosis at the referral level.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions will need to be developed for different scenarios such as involving active case finding, for example, during household contact studies, but this is outside the present scope of work. Evaluation of data from active case-finding studies, one as a cohort study with active follow-up [23] and the other as a community-based tuberculosis contact investigation study [24], have reported that 12% and 65%, respectively, of children with confirmed tuberculosis did not have clinical features consistent with the standardized "clinical signs/symptoms suggestive of tuberculosis" used to categorize clinical, unconfirmed cases. Active case finding is likely to identify cases at an earlier stage of disease and a much shorter duration of symptoms compared with children investigated for tuberculosis at the referral level.…”
Section: Discussionmentioning
confidence: 99%
“…When appropriate, investigators may wish to improve specificity by combining these case definitions with data from a clinical evaluation or prescription of treatment. One potential contributor to the observed discrepancies between NIH case definitions and clinical decision-making is that the NIH case definitions were not designed for the setting of active case finding [ 13 , 14 ], and some of children presented to health facilities following contact tracing activities. Another consideration is that NIH case definitions apply equal weight to each criterion, while clinicians may implicitly or explicitly weigh factors differently or consider factors beyond those noted in case definitions (eg, access to care).…”
Section: Discussionmentioning
confidence: 99%
“…As it has been demonstrated in MR, using many ostensible Mendelian factors where some are invalid may have the potential to improve the robustness of MFD analysis (Kang et al, 2016). Finally, the application of MFD to the study of vaccines against other childhood diseases that have unspecific symptoms and no gold-standard case definition, such as pediatric tuberculosis (Beneri et al, 2016) The World Health Organization (WHO) recommends that the primary endpoint in pivotal…”
Section: Discussionmentioning
confidence: 99%